Godard in the Karoo: J. M. Coetzee's Screenplay Adaptation of In the Heart of the Country. - Wittenberg, Hermann (English in Africa, 2014)
The article examines the screenplay adaptation written by J. M. Coetzee for his own novel "In the Heart of the Country." Topics covered include Coetzee's opinion on the influence of film editing on novelistic narration, the influence of 1960s avant-garde film on Coetzee's novel and the decision of director Marion Hansel to use his own screenplay for the 1985 film adaptation of the novel titled "Dust."